"Anti‐electrostatic" Halogen Bonding between Ions of Like Charge. Issue 67 (1st October 2021) - Holthoff, Jana M.; Weiss, Robert; Rosokha, Sergiy V.; Huber, Stefan M.
Abstract: Halogen bonding occurs between molecules featuring Lewis acidic halogen substituents and Lewis bases. It is often rationalized as a predominantly electrostatic interaction and thus interactions between ions of like charge (e. g., of anionic halogen bond donors with halides) seem counter‐intuitive. Herein, we provide an overview on such complexes. First, theoretical studies are described and their findings are compared. Next, experimental evidences are presented in the form of crystal structure database analyses, recent examples of strong "anti‐electrostatic" halogen bonding in crystals, and the observation of such interactions also in solution. We then compare these complexes to select examples of "counter‐intuitive" adducts formed by other interactions, like hydrogen bonding. Finally, we comment on key differences between charge‐transfer and electrostatic polarization. Abstract : This article provides an overview on halogen bonding (the noncovalent interaction between Lewis acidic halogen substituents and Lewis bases) between ions of like charge. Next to theoretical studies, experimental examples in the solid state and in solution are covered and a comparison with other interactions is provided.